Elderly in India: An Issue of Importance - Bhattacharyya, Arundhati (Advances in Social Sciences Research Journal, 2015)
The elderly population in the world is increasing. The elderly in all societies need special care and attention. The United Nations General Assembly endorsed the International Plan of Action on Ageing in 1982. The United Nations and the World Assembly on Ageing have generalized the boundary for defining old age to be 60 years. The paper is based on secondary sources and mentions some of the studies on the ageing population. Traditionally, India is a country which had special position for the aged in the family. But, the situation is slowly changing. Transition is taking place from joint to nuclear families, with the changing lifestyle of the people. Double-income nuclear families are slowly making the presence of the elderly redundant in their homes. The rising generation gap is creating havoc in the family relations. They are facing several forms of problems, which need to be addressed. The paper tries to provide an overview of the condition of the elderly